Beyond weight loss: Clinical anabolism to reduce muscle mass loss and physical function decline in patients undergoing pharmacological treatment for obesity - Câmara, Lucas Caseri; Ferreira, Matheus Hissa Lourenço (Revista ft, 2026)
The rapid expansion of anti-obesity pharmacotherapies, such as GLP-1 receptor agonists and GIP/GLP-1 co-agonists, has shifted the focus of obesity management toward substantial weight loss. In older adults and individuals with low lean mass reserve, however, weight loss often includes reductions in fat-free mass, declines in strength and performance, and potential skeletal costs—elements central to autonomy and quality of life. This article presents a clinical and pathophysiological rationale for complementing weight loss interventions with “clinical anabolism” (the therapeutic, protocol-driven, and monitored use of anabolic steroids), always in combination with resistance training and adequate protein-energy nutrition. The proposal is supported by robust indirect evidence from hypercatabolic states and the sarcopenic obesity phenotype, in which agents such as oxandrolone and nandrolone decanoate have demonstrated gains in lean mass and functional improvement under moderate-dose and time-limited regimens. Potential scenarios are specified (older adults undergoing anti-obesity pharmacotherapy, established sarcopenic obesity, disproportionate lean mass loss following more aggressive interventions), along with selection criteria, functional targets, and precautions to differentiate legitimate medical use from supraphysiologic abuse. Limitations are acknowledged (scarcity of specific randomized controlled trials in obesity with concomitant pharmacotherapy; androgenic, metabolic, and cardiovascular risks dependent on molecule/dose/duration), as well as the need for systematic clinical and laboratory monitoring. In summary, protecting muscle, bone, and function during weight loss may require combined strategies in which clinical anabolism, in well-selected subgroups, is considered an adjunct to optimize the “quality” of weight loss.